Viešosios tvarkos kategorija kaip arbitražą ir konkurencijos teisę siejantis veiksnys - Bron, Michail (Teisė, 2008)
This article on the basis of comparative analysis examines an unrevealed Lithuanian approach of the possibility to arbitrate the competition law issues. It is worth to remind about the article 11(1) provision of the Law on Commercial Arbitration of Lithuanian Republic, which expressly declares the bar to settle the dispute connected with the competition law. This paper provides the practice of foreign states and EC, where the competition law comes within the meaning of category of public policy. According to the international case-law public policy is extremely important, because it is a ground for arbitrating competition issues. Therefore recognition and implementation of arbitration awards in international practice may be at stake, if competition law is not applied. Consequently, despite the bar in Lithuania to arbitrate disputes related to competition it is advisable in Lithuanian practice to take into account possible risks of rejection of recognition or implementation of arbitral awards in foreign states on the grounds of public policy, which comprises competition.